The quality of doctoral education in South Africa: a question of significance - Jansen, Jonathan D. (Faculty of Education, University of the Free State, 2011)
One of the underlying concerns in the Study Panel on the South African PhD, a large-scale, overview investigation of the Academy of Science of South Africa (ASSAf), was the negative consequences of signalling the need for more doctoral graduates to boost the presumed link to national competitiveness within a global knowledge economy. There was evidence that institutional behaviour in response to increased incentives for more accredited publications led to increased quantity at the cost of quality. Understandably, therefore, the panel feared that policy signals and incentives to produce more doctorates would compromise quality PhDs from the 23 universities. At the heart of this concern was the significance of doctoral research and not simply more PhDs. This article seeks to advance thinking about how significance in doctoral research can be attained against the background of this national study, and its concerns, about quality PhDs.
Keywords: Higher education -- South Africa; Doctor of philosophy degree; Research